Size effect and phenomenological constitutive model of mechanical properties of ultra-thin 316L sheet - Wenlong Xie; Zonghui Su; Xiangcheng Zeng; Yong Xu; Siying Deng; Boris B Khina; Artur I Pokrovsky; Shihong Zhang (Materials Research Express)
To further enhance the fuel cell stack efficiency and reduce weight, the thickness of stainless steel bipolar plates is showing a decreasing trend, and the thickness of 0.075 mm is being considered. In this paper, 316L stainless steel with a thickness of 0.075 mm is taken as the research object. Different grain sizes were obtained and the effect of grain size on mechanical properties was studied. Based on the Swift hardening model, a phenomenological constitutive model containing t/d (ratio of plate thickness t to grain size d) was established. The flow stress shows a decreasing trend with the decrease of ${\rm{d}}^{\unicode{x02212}1/2}$ . When t/d ≥ 2.59, the flow stress follows the traditional Hall-Petch relation, while when t/d < 2.59, the flow stress deviates from Hall-Petch relation curve, and the size effect of ‘smaller is weaker’ appears. When t/d decreases, the deformation mechanism shifts from ‘dislocation-dominated within grains’ to ‘dominated by grain boundary/surface activity’. The increase of grain size reduces the obstruction of dislocation motion by grain boundaries, leading to a decrease in the strength coefficient $K$ . Dislocations in large grains move a longer distance within the grains, resulting in more dislocation proliferation and enhancing the strain hardening effect. Local strain concentration leads to a larger ${{ε }}_{0}$ to correct the nonlinear response in the initial stage of stress–strain curve in large grains. The calculated values of phenomenological constitutive model are in excellent agreement with the experimental values with maximum error of 0.024386. This research can provide material selection and finite element simulation support for lightweight ultra-thin stainless steel bipolar plate forming.